Otimização do desempenho de coroas cerâmicas monolíticas utilizando delineamento de experimentos - Ottoni, Rodrigo (2020)
The objective of this thesis is to evaluate the influence of the type of ceramic processing, abutment preparation and scanning method in the adaptation and mechanical behavior of lithium disilicate glass-ceramic (LD) monolithic crowns, using the statistical method of design of experiments (DOE). The study was divided into two scientific articles. The first article aimed to define the ideal combination of factors for all-ceramic crowns. Forty abutments preparations, chamfer (C) and rounded shoulder (S), were produced with a dentin analog material and digitized through extraoral (E) or intraoral (I) scanning. The captured images were processed using CAD software to design a premolar. LD glass ceramic blocks were milled in a CAD/CAM system (Cad). For the pressing technique (Press), the crowns were initially 3D printed using a polymeric material and the heat-pressing protocol was performed. DOE was used to plan the experimental groups. Adaptation was measured using the replica technique. The crowns were cemented with resin cement on the respective abutment and a compressive load was applied using a universal testing machine until fracture. Fractographic analysis was performed. ANOVA and statistical regression analysis were used to investigate the significant effects for each dependent variable, and the best combination of factors was calculated. The type of preparation and the scanning method did not influence the adaptation and fracture load of the crowns. Cad resulted in greater gap thickness in the occlusal area, axial and marginal angle and smaller thickness in the axial area; there was no effect of the ceramic processing method on the fracture load. The ideal combination of factors for all -ceramic crowns is chamfer preparation, extraoral scanning and Press technique (combined with 3D printing). The second article evaluated the adaptation and fatigue behavior of LD monolithic crowns produced by Cad and Press (combined with 3D printing) Thirty chamfer preparations were produced with a dentin analog material and digitized with an extraoral scanner; crowns were processed as described in article 1. The crowns were scanned using a micro-CT and images were processed to evaluate the adaptation. The fatigue test was performed on MTS machines (2 Hz, 37oC distilled water) using a compositeanatomical piston, following the step-stress method. The failures were detected with an acoustic system and confirmed by transillumination. The cumulative damage-Weibull distribution (95% CL) was used to analyze the fatigue data. Adaptation data were analyzed using two-wayANOVA and Tukey's post hoc test (α = 0.05). Cad resulted in greater gap thickness in the occlusal and smaller thickness in the axial angle and axial area. The fatigue failure probability was similar for Cad and Press. Radial cracks were the most frequent failure mode for both groups. LD crowns produced using the 3D printing/Press combination showed a more homogeneous gap thickness than crowns produced with Cad. However, the fatigue behavior was similar for both strategies used to produce monolithic LD crowns.